Relational aggression in sibling context : scale revision and factor analysis in a Taiwanese sample - Ong, Anna Wen Huey; Sanggari Krishnan; Wirawahida Kamarul Zaman (Penerbit Universiti Kebangsaan Malaysia, 2017)
The Forms and Functions of Aggression Questionnaire (Little, Jones, Henrich, & Hawley, 2003) is widely used to measure the aggressive behavior in the peer context by many researchers. It measures both overt and relational aggression, as well as two functions of aggressive behavior: reactive and instrumental. However, it focuses on the aggressive behavior in the peer setting, but not in the sibling context. The aim of this study was to adapt this scale in the sibling context. Respondents were 384 primary school students aged 10 to 12 years old who agreed to participate and met the inclusion criteria completed both measurements (The Forms and Functions of Aggression Questionnaire, and Sibling Inventory of Differential Experience). Confirmatory factor analysis confirmed a second-order model with three subdomains (pure relational aggression, reactive-relational aggression, and instrumental-relational aggression). Moderate and significant predictive validity was found. In sum, the Forms and Functions of Aggression Questionnaire is considered a suitable measure to be used in the sibling context with acceptable validity and reliability indices.